Comparative analysis of pathogenicity factors of closely related Mitis group streptococci and surface protein-containing antigens isolated from them - O. M. Afanasyeva; I. M. Gruber; D. S. Vorobyev; O. V. Zhigunova; M. N. Dmitrieva (Эпидемиология и вакцинопрофилактика)
Relevance. Mitis group streptococci (SMG) include 9 species of streptococci most frequently isolated from patients, including Streptococcus oralis and Streptococcus pneumoniae. The study of SMG shows not only differences but also overlaps in the genes encoding pathogenicity factors of S. pneumoniae and S. oralis. Earlier it was shown that antigens from S. pneumoniae serotype 6B induced cross-protective effect against virulent strains of S. pneumoniae. It was found that the experimental surface protein-containing fraction with molecular weight 30-100 kDa (PCF) from S. oralis has protective activity, stimulates in mice indicators of innate and adaptive immunity.Objective: to carry out a comparative analysis of pathogenicity factors of S. oralis and S. pneumoniae strains and protective activity of surface protein-containing antigens isolated from them.Materials and methods. The strains of S. oralis and S. pneumoniae serotype 6B Nos. 3353 and 1121 of different virulence were used. Experimental protein-containing antigens, in particular, PCF, were prepared from these strains. The protective activity of the obtained PCFs was evaluated in active protection experiments during intraperitoneal immunization and infection of BALB/c mice. Mass spectrometric study of PCF was carried out using UniProtKB database, taxon S. pneumoniae serotype 4 (strain ATCC BAA-334 / TIGR4.) Statistical processing of the results was carried out using parametric and nonparametric methods of comparison (p<0.05).Results and discussion. PCF from S. oralis has cross-species protective activity against virulent strains of S. pneumoniae of different serotypes, while PCF from S. pneumoniae strain 6B No. 3353 protects only against a virulent strain of the homologous serotype. Comparative analysis of genes encoding pathogenicity factors revealed differences: only in S. oralis genes encoding the synthesis of proteins promoting adhesion and biofilm formation (SspA, GtfD RlrA), and in S. pneumoniae strains - pore-forming toxin (Ply) and choline-binding protein (LytA) were identified. In the proteomic analysis of S. oralis and S. pneumoniae 6B No. 3353 PCFs, out of 673 identified proteins, 57 common proteins of most interest and 21 and 35 unique proteins, respectively, were selected for each PCF: in S. oralis PCFs, adhesion proteins were identified, as well as proteins related to metabolic systems and mediating the development of the infection process, while in S. pneumoniae PCFs, adhesion proteins were predominant those indirectly involved in the development of the infectious process, while the S. pneumoniae PCF is dominated by proteins related to the main pathogenicity factors.Conclusions. The surface protein-containing fraction 30 -100 kDa (PCF) isolated from a weakly virulent strain of S. oralis, belonging to the Mitis group streptococci, has interspecies protective activity against strains of closely related species - S. pneumoniae of different serotypes. PCF is capable of both preventing adhesion and colonization of pneumococcus and possibly playing the role of a natural adjuvant. In addition, it may be of interest to determine the protective effect of this antigen against other closely related SMG representatives. Both different and common genes encoding the synthesis of the main pneumococcal pathogenicity factors were identified in the strains, and unique proteins for each of them were determined by proteomic analysis of PCF.